(untitled) (Hackensack, N.J., 2004)
his book explores the interaction between Europe and East Asia between the 16th and the 18th centuries in the field of mathematical sciences, bringing to the fore the role of Portugal as an agent of transmission of European science to East Asia. It is an important contribution to understanding this fundamental period of scientific history, beginning with the arrival of Vasco da Gama in India in 1498 and ending with the expulsion of the Society of Jesus from Portugal in 1759. The former event opened a new era in relations between Europe and Asia, in particular regarding the circulation of scientific knowledge, leading to major social and intellectual changes in both continents. The Society of Jesus controlled education in Portugal and in the Empire. It was central to the network of knowledge transmission until the Society was expelled from Portugal in 1759.
Keywords: Mathematics,Mathematics,East Asia; History,History,Intellectual life,Western influences,History; East Asia,Portugal